Characterization of an outbreak due to extended-spectrum β-lactamase-producing Klebsiella pneumoniae in a neonatal intensive care unit - Pidal, Paola; Cona, Erna; Torrejón, Carolina; Airola, Contanza; Cifuentes, Javier; Ambiado, Sergio; Navarrete, Annette; Chacon, Eliana; Valderrama, Iris; Mihalic, Velimir; et al. (International Journal of Infection Control, 2021)
Background: The epidemiological–microbiological characteristics and effective intervention measures in an outbreak due to extended-spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae in a neonatal intensive care unit are described. Materials and methods: Cases from June 22, 2018 to February 11, 2019 were analyzed. Microbiological analysis of intestinal carriage of ESBL-producing K. pneumoniae and environmental samples was conducted. Strain relationships were studied by pulsed-field gel electrophoresis (PFGE). Results: A 35-week outbreak affecting 41 patients, with eight infected, 33 colonized, and two deceased patients occurred. Two stages of the outbreak were observed with differences in the frequency of intestinal carriage of ESBL-producing K. pneumoniae. The same genetic subtype was seen in patient strains and was different from strains isolated from the environment. Deficiencies in contact precautions, hand hygiene, and handling of breast milk were observed. Conclusions: A monoclonal outbreak by ESBL-producing K. pneumoniae that occurred in two phases and the different control measures in each of the stages is described. Effective control measures are mainly based on improving compliance with standard precautions and contact precautions, and other complementary measures are described such as proper handling of breast milk, periodic carriage studies, and the generation of three patient cohorts.